"SHINING BITS OF METAL": MONEY, PROPERTY, AND THE IMAGINATION IN HUME'S POLITICAL ECONOMY. Issue 1 (2020) - Costelloe, Timothy M.
Abstract: This essay examines Hume's treatment of money in light of his view of the imagination. It begins with his claim that money is distinct from wealth, the latter arising, according to vulgar reasoning, from the power of acquisition that it represents, or, understood philosophically, from the labor that produces it. The salient features that Hume identifies with the imagination are then put forth, namely its power to combine ideas creatively and the principle of easy transition that characterizes its movement among them. Two issues that these features explain are then discussed: first, why people take value to lie in the material of which money is made, and, second, why they assign value to what they take money to represent, namely, wealth. In both cases, the imagination creates a new relation, an illusion or fiction, that cannot be traced directly to experience. In the case of money, the faculty conjoins what is intangible (the power of acquisition) with the physical qualities of specie; in the case of property it produces a causal relation that connects persons with objects to constitute stable possession that constitutes ownership. Hume also appeals to the imagination to explain the rules of property that subsequently develop (present possession, occupation, prescription, and transference). The essay concludes by emphasizing that being based on the imagination is not in itself indicative of any instability in either money or property and the practices they enshrine, a feature they share with other phenomena (such as the self and continued existence) that Hume also traces to the same faculty.